Progress towards onchocerciasis elimination in the participating countries of the African Programme for Onchocerciasis Control: epidemiological evaluation results. Issue 1 (December 2016) - Tekle, Afework; Zouré, Honorath; Noma, Mounkaila; Boussinesq, Michel; Coffeng, Luc; Stolk, Wilma; Remme, Jan
Abstract Background The African Programme for Onchocerciasis Control (APOC) was created in 1995 to establish community-directed treatment with ivermectin (CDTi) in order to control onchocerciasis as a public health problem in 20 African countries that had 80 % of the global disease burden. When research showed that CDTi may ultimately eliminate onchocerciasis infection, APOC was given in 2008 the additional objective to determine when and where treatment can be safely stopped. We report the results of epidemiological evaluations undertaken from 2008 to 2014 to assess progress towards elimination in CDTi areas with ≥6 years treatment. Methods Skin snip surveys were undertaken in samples of first-line villages to determine the prevalence ofO. volvulus microfilariae. There were two evaluation phases. The decline in prevalence was evaluated in phase 1A. Observed and model-predicted prevalences were compared after correcting for endemicity level and treatment coverage. Bayesian statistics and Monte Carlo simulation were used to classify the decline in prevalence as faster than predicted, on track or delayed. Where the prevalence approached elimination levels, phase 1B was launched to determine if treatment could be safely stopped. Village sampling was extended to the whole CDTi area. Survey data were analysed within a Bayesian framework to determine if stopping criteria (overall prevalence <1.4 % and maximum stratum prevalence <5 %) were met. Results In phase 1A 127 665 people from 639 villages in 54 areas were examined. The prevalence had fallen dramatically. The decline in prevalence was faster than predicted in 23 areas, on track in another 23 and delayed in eight areas. In phase 1B 108 636 people in 392 villages were examined in 22 areas of which 13 met the epidemiological criteria for stopping treatment. Overall, 32 areas (25.4 million people) had reached or were close to elimination, 18 areas (17.4 million) were on track but required more years treatment, and in eight areas (10.4 million) progress was unsatisfactory. Conclusions Onchocerciasis has been largely controlled as a public health problem. Great progress has been made towards elimination which already appears to have been achieved for millions of people. For most APOC countries, nationwide onchocerciasis elimination is within reach.